The Oxford handbook of the South African economy - Oqubay, Arkebe; Tregenna, Fiona; Valodia, Imraan (Oxford : Oxford University Press, 2021)
While sharing some characteristics with other middle-income countries, South Africa is a country with a unique economic history and distinctive economic features. It is a regional economic powerhouse that plays a significant role, not only in southern Africa and in the continent, but also as a member of BRICS. However, there has been a lack of structural transformation and weak economic growth, and South Africa faces the profound triple challenges of poverty, inequality, and unemployment. Any meaningful debate about economic policies to address these challenges needs to be informed by a deep understanding of historical developments, robust empirical evidence, and rigorous analysis of South Africa's complex economic landscape. This volume seeks to provide a wide-ranging set of original, detailed, and state-of-the-art analytical perspectives that contribute to scientific knowledge.
Challenges and Complexities of the South African Economy / Arkebe Oqubay, Arabo K. Ewinyu, Fiona Tregenna, Imraan Valodia -- Agriculture in South Africa / Wandile Sihlobo, Johann Kirsten -- Agro-processing industries in the South African economy / Horman Chitonge -- Land and agrarian development in South Africa / Ruth Hall, Farai Mtero -- Mining and minerals in South Africa / Neva Seidman Makgetla -- Energy in South Africa / Rod Crompton, Ruwadzano Matsika -- Socioeconomic aspects of energy and climate change in South Africa / Roula Inglesi-Lotz -- Climate change and the green transition in South Africa / Channing Arndt, Sherwin Gabriel, Faaiqa Hartley, Kenneth Marc Strzepek, Timothy S. Thomas -- Corporate structure, industrial development, and structural change in South Africa / Pamela Mondliwa, Simon Roberts -- Value chains and industrial development in South Africa / Mike Morris, Justin Barnes, David Kaplan -- Entrepreneurship and SMMEs in South Africa / Boris Urban -- The economic history of South Africa before 1948 / Stefan Schirmer -- Innovation and technological change in South Africa / Erika Kraemer-Mbula, Rasigan Maharajh -- South Africa and the fourth industrial revolution / Bhaso Ndzendze, Tshilidzi Marwala -- Industrial policy in South Africa / Anthony Black -- Competition policy in South Africa / Liberty Mncube, Nicola Theron -- Regulation of network industries in South Africa / James Hodge, Tamara Paremoer -- State-Owned Enterprises in South Africa / Mark Swilling, Nina Callaghan -- Black economic empowerment in South Africa / Thando Vilakazi -- Urbanisation, agglomeration, and economic development in South Africa / Ivan Turok -- Changing dynamics in the South African labour market / Haroon Bhorat, Ben Stanwix, Amy Thornton -- The Economic History of South Africa 1948-1994 / Bill Freund, Vishnu Padayachee -- The youth labour market in South Africa / Cecil Mlats
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from PDF title page (viewed on December 6, 2021).
Keywords: South Africa -- Economic conditions; South Africa -- Economic policy